Empreendedorismo, colaboração e coworking : análise dos discursos do Impact Hub São Paulo e de seus membros - Spina Junior, Marcelo May (2017)
This research has as its theme the collaborative work and the entrepreneurial activity within the Impact Hub São Paulo, a coworking company whose mission is to provide a focused on entrepreneurial productivity through collaboration, exchange of experiences and networking among different projects. We aim to entrepreneurship (such as work, culture and style of life) and collaborative work, in addition to their meanings and relevance in the contemporary world - especially for members of Impact Hub São Paulo. To this end, research theoretical approach to French line discourse analysis (ORLANDI, 1999) for understand the symbolic production and ideology present in the Impact Hub communication. Subsequently, through the application of semi-structured interviews (BONI, QUARESMA, 2005), an analysis of the Hub's own speeches on the work collaborative and also the consumer relations that occur within the space itself. O theoretical framework that supports this empirical work is based on authors such as Boltanski and Chiapello (2009), Sennett (2005, 2006, 2009, 2012), Ehrenberg (2010), Han (2013, 2015) Gaulejac (2007), Casaqui (2014, 2015a, 2015b, 2016a, 2016b), among others. According to analysis of the results, we understand that Impact Hub São Paulo seeks to position itself as a space that promotes collaborative relationships among its members with the promise of that each project will present a better business performance and that, therefore, these projects will build a "better world" through social impact. However, from the analysis of discourses of its members, we understand that the working relationships within this space are not, in fact, collaborative relationships and that the call to build a "new world" "collaborative work of high impact" is merely a part of the rhetoric of capitalism in order to engage individuals in this mode of production.